Dampak Kuantitas Akrual, Volatilitas Arus Kas Operasi dan Tingkat Utang Terhadap Persistensi Laba - Yoana, Fransesca; Tarigan, Thia Margaretha; Prasetyo, Christianus Yudi (Universitas Muhammadiyah Jakarta, 2024)
Objectives: To analyze the effect of accrual quantity, operating cash flow volatility, and debt level on profit persistence in financial sector companies in 2018-2022.Design/method/approach: The research sample uses panel data with purposive sampling technique of 59 companies listed on the Indonesia Stock Exchange through the website www.idx.co.id. Data processing uses multiple linear regression methods to test the influence between variables.Results/findings: The findings indicate that the quantity of accruals and operating cash flow volatility have little bearing on profit persistence, but that debt levels do.Theoretical contribution: Signal theory is a theoretical reference in this research that can provide knowledge for companies to maintain the stability of company profits so that it becomes a good signal for investors.Practical contribution: From the research results, it is expected that companies will pay attention to the quantity of accruals, cash flow volatility, and debt levels so that they can maintain the persistence of company profits.Limitations: This research is limited to financial sector companies for the years 2018-2022.